Sport facility and event management - Aicher, Thomas J.; Paule-Koba, Amanda L.; Newland, Brianna L. (Burlington : Jones & Bartlett Learning, 2016)
The book focuses on the major components of both facility and event management planning, financing, marketing, implementation, and evaluation. It integrates theoretical foundations with real world practicality and application to provide the reader with a strong foundation in facility and event management. The authors focus on a range of facilities and events to demonstrate the diversity of the industry, which encompasses recreation, leisure, health and fitness, in addition to the more commonly discussed sport facilities and events.
Chapter 1. Introduction and History -- Chapter 2. Management Theory -- Chapter 3. Facility Design and Construction -- Chapter 4. Finance and Budgeting -- Chapter 5. Bidding and Planning for Different Events -- Chapter 6. Designing the Event Experience -- Chapter 7. Project Management and Event Implementations -- Chapter 8. Marketing the Facility and Events -- Chapter 9. Consumer Behavior -- Chapter 10. Sponsorship -- Chapter 11. Traditional Revenue Generation in Sport and Recreation -- Chapter 12. Consumer Service -- Chapter 13. Risk Management --Chapter 14. Measurement and Evaluation -- Chapter 15. Sustainability and Legacy.
Includes bibliographical references and index.
Keywords: SPORTS FACILITIES -- MANAGEMENT; SPECIAL EVENTS -- MANAGEMENT